Aryl Urea Based Scaffolds for Multitarget Drug Discovery in Anticancer Immunotherapies - Celia Martín-Beltrán; Raquel Gil-Edo; Germán Hernández-Ribelles; Raül Agut; Pilar Marí-Mezquita; Miguel Carda; Eva Falomir (MDPI AG, 2021)
Twenty-one styryl and phenethyl aryl ureas have been synthetized and biologically evaluated as multitarget inhibitors of Vascular endothelial growth factor receptor-2 VEGFR-2 and programmed death-ligand-1 (PD-L1) proteins in order to overcome resistance phenomena offered by cancer. The antiproliferative activity of these molecules on several tumor cell lines (HT-29, MCF-7, HeLa and A549), on the endothelial cell line human microvascular endothelial cells (HMEC)-1 and on the non-tumor cell line human embryonic kidney cells (HEK)-293 has been determined. Some derivatives were evaluated for their antiangiogenic properties such as their ability to inhibit microvessel formation using HMEC-1 or their effect on VEGFR-2 in both cancer and endothelial cell lines. In addition, the immunomodulator action of a number of selected compounds was also studied on PD-L1 and c-Myc proteins. Compounds 16 and 23 (Z) and (E)-styryl p-bromophenyl urea, respectively, showed better results than sorafenib in down-regulation of VEGFR-2 and also improved the effect of the anti-PD-L1 compound BMS-8 on both targets, PD-L1 and c-Myc proteins.